UPAYA PENINGKATAN PROFESIONALISME GURU MELALUI PROGRAM SERTIFIKASI DI SDN 7 SINGKAWANG - Rheza Raviandi E.01109010 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article raises issues in certification program in improving performance und incentives teacher, and has not fully qualified bachelor's degree in public elementary school 7 singkawang. The problems in face not fully performance improvement teacher goes well, professionalism often it seems that fund allowance the profession of a teacher an impact on the performance of a teacher. I have still many teachers who do not meet academic qualifications a university degree. This article is intended to provide an understanding of the implementation of the certification of teachers so that teachers can be profesonalisme improvement objectives are achieved as a result of the expected. This research included in this type of descriptive study with a qualitative paradigm. based on the research conducted, the author concludes that the implementation of the certification on the run in primary school the country 7 singkawang already can be said to be doing well. In terms of the implementation process runs smoothly and could be said to be a success, so that the perceived impact of the results of these policies is capable of delivering prosperity and improve the performance of teachers. Suggestions for research is. teachers are expected to further improve the quality of her ability in delivering the learning process by improving academic qualifications so that the awarding of this certification is no longer based on the age of the average minimum is S1. Keywords: program certification, professionalism of teacher, improving education